The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1029/2018jc014026
|View full text |Cite
|
Sign up to set email alerts
|

On the Modified Circumpolar Deep Water Upwelling Over the Four Ladies Bank in Prydz Bay, East Antarctica

Abstract: Analyses of hydrographic observation data sets revealed that modified Circumpolar Deep Water (mCDW) tends to flood the western flank (73–78°E, 67–68°S) of the Four Ladies Bank (FLB) in Prydz Bay. In this study, we investigated the mechanism responsible for mCDW upwelling over the FLB based on an eddy‐resolving coupled ocean‐sea ice‐ice shelf model in conjunction with the latest high‐accuracy bathymetry. It was found that zonal step‐like declines in the seabed over the FLB are crucial for the mCDW onshore upwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 66 publications
2
57
0
Order By: Relevance
“…Although the Antarctic Slope front (ASF) acts as a strong dynamical barrier to the inflow of CDW across the shelf in East Antarctica (Spence et al, ; Thompson et al, ), intrusions of mCDW have been observed in the sea ice growth season (March–August), entering Prydz Bay over Four Ladies Bank (FLB) and occupying the eastern side of the bay following the cyclonic PBG and are directed toward the eastern flank of the AIS (Herraiz‐Borreguero et al, ; Liu et al, ; Williams et al, ). The interaction of the AIS with mCDW heat transport has been clarified by several studies (Herraiz‐Borreguero et al, , ; Wong et al, ), and the AIS net basal melt rate driven by mCDW inflow was estimated at 1.0 ± 0.4 m/year (Herraiz‐Borreguero et al, ), reducing local shelf water density and suppressing its potential contribution to AABW formation (Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Antarctic Slope front (ASF) acts as a strong dynamical barrier to the inflow of CDW across the shelf in East Antarctica (Spence et al, ; Thompson et al, ), intrusions of mCDW have been observed in the sea ice growth season (March–August), entering Prydz Bay over Four Ladies Bank (FLB) and occupying the eastern side of the bay following the cyclonic PBG and are directed toward the eastern flank of the AIS (Herraiz‐Borreguero et al, ; Liu et al, ; Williams et al, ). The interaction of the AIS with mCDW heat transport has been clarified by several studies (Herraiz‐Borreguero et al, , ; Wong et al, ), and the AIS net basal melt rate driven by mCDW inflow was estimated at 1.0 ± 0.4 m/year (Herraiz‐Borreguero et al, ), reducing local shelf water density and suppressing its potential contribution to AABW formation (Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be assumed that ocean circulation and tides are key drivers for sea ice stability in the Southern Ocean. According to, for example, Tamsitt et al (2017) and Liu et al (2018), upwelling of deeper water masses can be expected along the shelf break. Tides apparently have a great influence on the stability of the sea ice.…”
Section: Discussionmentioning
confidence: 99%
“…A narrow Antarctic Coastal Current (ACoC), driven by offshore and easterly winds, flows westwards near to the coast (Smith et al, 1984). Intrusion of Modified Circumpolar Deep Water (MCDW) occurs over Four Ladies Bank and eventually flows into the Prydz Bay Gyre and the AIS cavity (Galton-Fenzi et al, 2012;Liu et al, 2018). This MCDW is an important factor in driving basal melting of the AIS (Herraiz-Borreguero et al, 2015).…”
Section: Sørsdal Glacier Ice Shelf Regionmentioning
confidence: 99%
“…Observations from APRES confirm this and show that a seasonal cycle in basal melting is practically nonexistent at the two sampled sites. However, despite the weak observed melting, observations from moorings, ship, and instrumented seals over many years (Guo et al, 2019;Nunes Vaz & Lennon, 1996;Smith et al, 1984;Williams et al, 2010Williams et al, , 2016Wong et al, 1998) and multiple modeling studies (Galton-Fenzi et al, 2012;Liu et al, 2017Liu et al, , 2018 of the Prydz Bay region have shown that MCDW upwells over the Four Ladies Bank and is present close to the coastline in significant quantity. This MCDW has been shown to (in part) drive melting beneath the AIS (Herraiz-Borreguero et al, 2013;Herraiz-Borreguero et al, 2015) and is known to drive strong melt in other locations around Antarctica (e.g., Walker et al, 2013).…”
Section: Weak Basal Melting Beneath the Sørsdal Ice Shelfmentioning
confidence: 99%